The lenient treatment of honor crimes in Egypt - Zaid, Mohamed Diaaeldin (AUC Knowledge Fountain, 2015)
Scholars often assume that Arab legislation including Egypt accommodates honor crimes. Two pieces of Egyptian legislation that receive attention are Article 237 which reduce the sanction to the husband who kills his adulterous wife upon committing adultery, and Article 17 which empowers courts in felonies to give leniency whenever they see appropriate. They believe that Article 237 of the Egyptian penal code limits the reduction in sanctions to the husbands while excluding other male paternal relatives. To accommodate this exclusion, they assume that Article 17 of the penal code indirectly entrenches the scope of protection to cover other male relatives and not only husbands. In their minds, this guarantees the perpetrators of honor crimes lenient punishment constituting a safe escape from serious prosecution. An examination of approximately 1,550 appeals submitted before the Egyptian Court of Cassation from 1934 to 2014 that involve the application of Article 17 of the penal code challenges these assumptions. It shows that the leniency of courts is not necessarily applied every time a crime of honor is brought before them. The examination of the appeals submitted before the Egyptian Court of Cassation assumes that honor crimes are not necessarily the most common crimes to which the leniency of the judiciary is applied. Leniency is assumed to be applied to other crimes including murders not involving honor, illicit possession of drugs and weapons, bribery and several others. This research concludes that leniency is assumed to be often given to a wide range of crimes including crimes involving honor.